"We Don't Feel so Alone": A Qualitative Study of Virtual Memory Cafés to Support Social Connectedness Among Individuals Living With Dementia and Care Partners During COVID-19 - Sara S. Masoud; Kylie N. Meyer; Lauryn Martin Sweet; Lauryn Martin Sweet; Patricia J. Prado; Patricia J. Prado; Carole L. White (Frontiers Media S.A., 2021)
Introduction: Loneliness and low social support can be detrimental to the health of individuals living with Alzheimer's and related dementias (ADRD) and family care partners. Restrictions on gatherings to prevent the spread of COVID-19 create an even greater risk for social isolation. Memory Cafés are a highly replicated program that provide individuals living with ADRD and care partners an opportunity to socialize in an inclusive and supportive environment without fear of judgment, pressure, or stigma. Following restrictions on in-person gatherings, virtual Memory Cafés offer regular social engagement opportunities in an online format. While the Memory Café model has been replicated globally, their effects on loneliness and perceived social support are generally unknown. Even less is known about their impact when operating in a virtual environment.Methods: Semi-structured interviews in Spanish and English were conducted with individuals living with dementia and family care partners who regularly attend Memory Cafés hosted by partners in a Texas Memory Café Network. Interviews took place online using video conferencing software, were transcribed, then analyzed for common themes using a combined inductive and deductive approach.Results: A total of 17 interviews were conducted with persons living with dementia (n = 5) and family care partners (n = 12) who attend Memory Cafés to learn about their perceived experiences of social connectedness since COVID-19. Care partners included spouses (n = 8) and adult children (n = 4). Interviews included attendees of different Memory Café models, including in-person only (n = 2), virtual only (n = 9), and those who attend both models (n = 6). Five key themes were identified: (1) Reprieve; (2) What is still possible; (3) Connectedness; (4) Inclusivity; and (5) Value added, with ten sub-themes supporting these main themes.Discussion: Findings substantiate evidence that Memory Cafés offer important benefits for families living with dementia, providing vital new insight into the potential for virtual Memory Cafés to offer similar benefits. Findings have implications beyond the context of COVID-19, where virtual models may support the social connectedness of those living in geographically marginalized and underserved areas. Virtual models may not address the needs of all families experiencing dementia due to lack of access to technology and limitations for virtual engagement with those experiencing later stage dementia.